PROTOTYPE PERANCANGAN SISTEM OTOMATIS PEMBACA SUHU RUANGAN MENGGUNAKAN OUTPUT KIPAS DAN SENSOR LM35 BERBASIS MIKROKONTROLER ATMEGA 16 - Ageng Setiani Rafika; Sudaryono Sudaryono; Wisnu Dwi Andoyo (Universitas Raharja, 2015)
The fan is a tool that we usually find in everyday life. This is because the fan is a tool commonly used to lower the temperature or refrigerate something. However, the current use of the fan can be developed into a cooling device that can be controlled using an electronic device such as a microcontroller. Therefore we need a system for room temperature control in order to create a good temperature in conducting cooling system. Not just make the climate control, but also made the monitoring system. The data obtained from the LM35 temperature sensor is processed and then displayed in real time in the form of graphs and tables that can be seen by the computer using an LCD that can show the actual temperature in a room that has been installed LM35 sensor. Atmega16 microcontroller used is an 8-bit microcontroller which has a high capability and low power, in addition to all of the instructions executed in one clock cycle. AVR has 32 general-purpose registers, timer / counters flexible with compare modes, internal interrupt and power saving mode, the internal ADC and PWM. AVR also has in programmable system-on-chip flash program memory allows the system to be re-programmed using the serial SPI relationship.